2011
DOI: 10.1002/jso.21940
|View full text |Cite
|
Sign up to set email alerts
|

Surgical implications of mesenteric lymph node metastasis from advanced ovarian cancer after bowel resection

Abstract: Resection of regional lymph nodes of affected organs that is similar to surgical procedures that are performed for colorectal carcinoma is an appropriate, optimal debulking surgery for patients with ovarian carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 52 publications
(60 reference statements)
3
12
1
Order By: Relevance
“…Second, we found a 42.3 % metastatic spread to mesenteric lymph nodes, in keeping with another study [16]. Other authors report figures that differ significantly from ours [15,17] and correlate it to certain pathologic variables, such as depth of colorectal-wall invasion [15], spread to retroperitoneal lymph nodes [17], or both [18], or the amount of the large bowel resected [14]. In our experience, whenever metastatic peritoneal spread invades the colorectal wall, one can reasonably expect mesenteric lymph node metastasis equal to or more frequent than that found in the pelvic and interaortocaval (locoregional) stations.…”
Section: Pathologysupporting
confidence: 88%
“…Second, we found a 42.3 % metastatic spread to mesenteric lymph nodes, in keeping with another study [16]. Other authors report figures that differ significantly from ours [15,17] and correlate it to certain pathologic variables, such as depth of colorectal-wall invasion [15], spread to retroperitoneal lymph nodes [17], or both [18], or the amount of the large bowel resected [14]. In our experience, whenever metastatic peritoneal spread invades the colorectal wall, one can reasonably expect mesenteric lymph node metastasis equal to or more frequent than that found in the pelvic and interaortocaval (locoregional) stations.…”
Section: Pathologysupporting
confidence: 88%
“…For example, Park et al related malignant mesenteric lymph node spread to the depth of colorectal wall invasion [31], Salani et al to retroperitoneal lymph-node spread [33] and Lax et al to the amount of colorectum resected [28]. In their later study Baiocchi et al found a significant correlation between mesenteric lymph node spread and the depth of colorectal wall invasion and the presence of metastases at the retroperitoneal lymph node stations [34]. Our experience underlines that whenever metastatic peritoneal spread in advanced ovarian cancer invades the colorectal wall, one can reasonably expect mesenteric lymph node involvement equal to or even greater than that in the typical pelvic and interaortocaval locoregional lymph node stations (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a series of total pelvic exenteration for recurrent gynecological cancer, Sardain et al16 and Mourton et al17 reported that the rate of mesorectal nodal metastasis was 19% and 10%, respectively. They also found that MRNM is common in patients with rectal wall involvement in recurrent cervical cancer as well as ovarian cancer 18. This is understandable as rectal cancers normally drain into into the mesorectal lymph nodes.…”
Section: Discussionmentioning
confidence: 93%